Highly Efficient Polydopamine-coated Poly(methyl methacrylate) Nanofiber Supported Platinum–Nickel Bimetallic Catalyst for Formaldehyde Oxidation at Room Temperature - He, Fa-Gui (Polymers (Basel), 2019)
We fabricated one fibrous-membrane type of flexible and lightweight supported catalyst via loading platinum–nickel nanoparticles (PtNi NPs) directly on the polydopamine-coated polymethylmethacrylate electrospun-fibers (PMMA@PDA). The polymer support with the PDA layer provided numerous active sites, leading to well-monodispersed and sized PtNi NPs on the nanofibers. Through the rational design of PtNi NPs, the resultant catalyst system exhibited 90% conversion for decomposing HCHO (10 ppm) at room temperature with only a low dosage (0.02 g), retaining the high activity for 100 h. This superior catalytic performance stems from the formate oxidation, which was the key intermediate during HCHO decomposition, and was promoted by the existence of a sufficient Pt–OH–Ni interface in the PtNi NPs with an appropriate Pt/Ni ratio of 1:5. Such tailored Pt-based nanoparticles ideally work together with the polymer nanofibers as a support for catalytic reaction. Compared with classical catalysts, our system can handle a comparable efficiency with much lower air resistance and remarkably lower dosage. Furthermore, the membrane-like morphology provides easy handling and minimizes the leaching of catalyst nanoparticles.